Effects of Carboxymethyl Cellulose Sodium/Polyvinyl Pyrrolidone and Heracleum hemsleyanum Diels Extract Composite Coating on Storage Quality of Citrus - Boyun ZHANG; Yu ZHANG; Qingshan LI; Xuefeng GAO; Jiao LI; Junjie KOU; Fengbo XU (Shipin gongye ke-ji, 2022)
''Gannan navel orange'' was used as the test fruit, the effects of the solution of Heracleum hemsleyanum Diels extracts，carboxymethyl cellulose sodium/polyvinyl pyrrolidone and γ-aminobutyric acid with different concentrations on citrus fruit fresh-keeping were studied by response surface methodology with decay rate, weight loss rate and the content of ascorbic acid as evaluation parameters. And then the best formula was determined and its fresh-keeping effects on citrus were explored. The optimal formulation was determined as follow: The concentration of Heracleum hemsleyanum Diels extracts, carboxymethyl cellulose sodium/polyvinyl pyrrolidone and γ-aminobutyric acid were 2.0%, 0.6%/0.4% and 1.0%, respectively. The experimental results of the fresh-keeping effect test can be obtained：Compared with the control group, adding the Heracleum hemsleyanum Diels extracts could significantly reduce the decay rate, delay the decrease of fruit hardness, and keep the activities of superoxide dismutase and β-1,3-glucanase, reduce the content of malondialdehyde. The composite coating could prevent the loss of water in citrus fruits, and keep soluble solids, titratable acid, ascorbic acid and total sugar content, and maintain fruit flavor. The combination of the two components to prepare composite coating preservative could play a role of effect superposition, the comprehensive fresh-keeping effect is better than the two alone.